1983
DOI: 10.2307/1590316
|View full text |Cite
|
Sign up to set email alerts
|

Virus Isolations from Pet Birds Submitted for Importation into the United States

Abstract: From October 1973 to September 1981, 2,882,111 birds were offered for importation into the United States. All were quarantined for 30 days, and specimens were submitted to the laboratory for virus-isolation studies. Viruses were isolated from specimens from 26.3% (598/2,274) of the quarantined lots of birds. Viscerotropic velogenic Newcastle disease virus (VVNDV) was isolated from 141 lots. Nonviscerotropic velogenic Newcastle disease virus (VNDV) was isolated from six lots. All VVNDV- and VNDV-positive lots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 3 publications
1
29
0
1
Order By: Relevance
“…This clearly suggested that imported caged birds have contributed to the distribution of NDV, including the outbreaks involving NDV genotype V, which was introduced by imported infected psittacines (39). Many NDVs have been isolated from caged birds worldwide (4,5,8,15,28,35). Since the trading of these birds across regional and international boundaries is extensive (over 400,000 nonpoultry birds have been imported into Japan each year for the last 5 years), the risk of worldwide dissemination of potentially virulent NDVs is considerable.…”
mentioning
confidence: 99%
“…This clearly suggested that imported caged birds have contributed to the distribution of NDV, including the outbreaks involving NDV genotype V, which was introduced by imported infected psittacines (39). Many NDVs have been isolated from caged birds worldwide (4,5,8,15,28,35). Since the trading of these birds across regional and international boundaries is extensive (over 400,000 nonpoultry birds have been imported into Japan each year for the last 5 years), the risk of worldwide dissemination of potentially virulent NDVs is considerable.…”
mentioning
confidence: 99%
“…APMV-2 viruses also have been frequently isolated from passerine and psittacine birds. Surveillance of wild birds has indicated that APMV-2 viruses are more frequent in passerines (Alexander, 1986;Senne et al, 1983). APMV-2 infection was shown to affect hatchability and poult yield in turkeys (Bankowski et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…APMV-2 strains have also frequently been isolated from passerine and psittacine birds. Surveillance of wild birds has indicated that APMV-2 infections are more frequent in passerines (3,35).…”
mentioning
confidence: 99%